Advances in materials-based therapeutic strategies against osteoporosis. (May 2023) - Lei, Chen; Song, Jing-han; Li, Song; Zhu, Yi-na; Liu, Ming-yi; Wan, Mei-chen; Mu, Zhao; Tay, Franklin R.; Niu, Li-na
Abstract: Osteoporosis is caused by the disruption in homeostasis between bone formation and bone resorption. Conventional management of osteoporosis involves systematic drug administration and hormonal therapy. These treatment strategies have limited curative efficacy and multiple adverse effects. Biomaterials-based therapeutic strategies have recently emerged as promising alternatives for the treatment of osteoporosis. The present review summarizes the current status of biomaterials designed for managing osteoporosis. The advantages of biomaterials-based strategies over conventional systematic drug treatment are presented. Different anti-osteoporotic delivery systems are concisely addressed. These materials include injectable hydrogels and nanoparticles, as well as anti-osteoporotic bone tissue engineering materials. Fabrication techniques such as 3D printing, electrostatic spinning and artificial intelligence are appraised in the context of how the use of these adjunctive techniques may improve treatment efficacy. The limitations of existing biomaterials are critically analyzed, together with deliberation of the future directions in biomaterials-based therapies. The latter include discussion on the use of combination strategies to enhance therapeutic efficacy in the osteoporosis niche. Graphical abstract: Image 1